Knowledge, Attitude and Willingness to Participate in Gamete Donation for Artificial Insemination among Undergraduate Students in Lagos - Bakare OQ; Oluwole OE; Ogunkoya D; Aja C; Thomas J (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Background: Infertility affects one-fifth to one-sixth of couples of reproductive age. Gamete donation is one option for managing infertility, but it is relatively unknown in the developing world. Objectives: To assess Nigerian undergraduate students' knowledge, attitude and willingness to participate in gamete donation for artificial insemination. Methods: A descriptive cross-sectional study was conducted among 160 undergraduate students using a semi-structured self-administered questionnaire. The respondents were recruited using a multi-stage sampling technique. Results: The mean age of the respondents was 21.5±3.2 years, with a range of 18-32 years. The majority (89.4%) of the respondents were single and were in the first year of study (56.3%). Almost all the respondents (96.3%) had heard about the practice of gamete donation, but only (38.7%) had overall good knowledge about it. Almost half (46.9%) of respondents had an overall positive attitude towards gamete donation, while only 37.5% were willing to participate. The class level of the respondents (p = 0.03) was significantly associated with poor knowledge of gamete donation, while age (p = 0.01) and gender (p < 0.001) were associated with a negative attitude. Age (p<0.001) was also significantly associated with poor willingness to participate. Conclusion: The respondents' awareness of gamete donation was high, but their knowledge was poor, leading to a negative attitude and poor willingness to participate. Public enlightenment on gamete donation for artificial insemination should be intensified.